Promising Anticancer Activity of Pyrazole Compounds against Glioblastoma Multiforme: Their Synthesis, In vitro, and Molecular Docking Studies - Nalcı, Kemal Alp; Mete, Cihat; Demir, Zeynep; Bildirici, İshak and Cetin, Adnan (Medicinal Chemistry, 2025)
BackgroundGlioblastoma Multiforme (GBM), a highly aggressive and prevalent brain cancer with a higher incidence in males, has limited treatment success due to drug resistance, inadequate targeting and penetration of cancer cells, and an incomplete understanding of its molecular pathways. GBM is a highly aggressive brain cancer with limited treatment options. This study investigates the anticancer potential of synthesized pyrazole compounds against GBM cells.MethodsA series of pyrazole derivatives were synthesized and tested for their efficacy against GBM using MTT assays. Molecular docking studies were conducted to explore the binding interactions of these compounds with GBM receptors.ResultsCompounds 3 and 5 demonstrated significant anticancer activity, reducing cell viability more effectively than the control group. MTT assay results confirmed their potency. Molecular docking studies revealed strong binding interactions with GBM receptors, highlighting their potential as anticancer agents.ConclusionThe study evaluated the anticancer activity of synthesized compounds on human GBM cells, with compounds 3 and 5 showing the most promising results. Pyrazole 3 significantly reduced cell viability at high concentrations, while both pyrazoles 3 and 5 required higher doses to achieve substantial effects, as indicated by their IC50 values. Molecular docking studies confirmed strong binding interactions with the GBM receptor, and the pharmacokinetic properties suggest their potential as anticancer agents. These results highlight compounds 3 and 5 as candidates for further investigation.
Keywords: brain diseases